2019
DOI: 10.1111/cas.13984
|View full text |Cite
|
Sign up to set email alerts
|

Testis‐specific protein, Y‐linked 1 activates PI3K/AKT and RAS signaling pathways through suppressing IGFBP3 expression during tumor progression

Abstract: The testis‐specific protein, Y‐linked 1 ( TSPY 1), a newly recognized cancer/testis antigen, has been suggested to accelerate tumor progression. However, the mechanisms underlying TSPY 1 cancer‐related function remain limited. By mining the RNA sequencing data of lung and liver tumors from The Cancer Genome Atlas, we found frequent ectopic expression of TSPY 1 in lung adenocarcinoma ( LUAD ) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…[ 26 ] However, IGFBP3 is also known to repress tumor progression and metastasis through the inactivation of PI3K/AKT and RAS signaling pathways. [ 27,28 ] We previously reported that the E3 ligase TRAIP promotes osteosarcoma tumor growth via KANK1‐IGFBP3‐AKT signaling. [ 19 ] In this study, we further show that PD‐L1 binds with IGFBP3 to activate mTOR signaling in osteosarcoma.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26 ] However, IGFBP3 is also known to repress tumor progression and metastasis through the inactivation of PI3K/AKT and RAS signaling pathways. [ 27,28 ] We previously reported that the E3 ligase TRAIP promotes osteosarcoma tumor growth via KANK1‐IGFBP3‐AKT signaling. [ 19 ] In this study, we further show that PD‐L1 binds with IGFBP3 to activate mTOR signaling in osteosarcoma.…”
Section: Resultsmentioning
confidence: 99%
“…Several CTAs of our panel, such as the MAGE-family members, CTAG1B, TSPY1, and CAGE1, are functionally involved in tumorigeneses and cancer progression by modulating gene expression, regulating mitosis, and tumorigenic signaling [8,10,[36][37][38]. More specifically, MAGE-A9 and TSPY have been shown to be involved in HCC tumor cell proliferation [36,38].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies demonstrated that TSPY1 has physiological functions in the proliferation and differentiation of spermatogonia during spermatogenesis [ 15 ]. Remarkably, TSPY1 is also involved in the initiation and development of many tumors by activating the PI3K/AKT and RAS signaling pathways by suppressing IGFBP3 expression [ 16 ]. Amelogenins are useful for sex identification and are involved in biomineralization during tooth enamel development [ 17 ].…”
Section: Discussionmentioning
confidence: 99%